(untitled) (Journal of Parents and Teachers, 2016)
This article concerns the importance of the different participants which interact in the educational sector. It highlights the importance of the figure of the PT when it comes to integrating students within the school and encouraging diversity. Besides this, we have begun to utilize new technologies in the classroom with the goal that education and technology go hand in hand being that both are consistent with the society in which we live.